Biomedical Informatics - Shortliffe, Edward H.; Cimino, James J. (Springer, 2014)
The world of biomedical research and health care has changed remarkably in the 25 years since the fi rst edition of this book was undertaken. So too has the world of computing and communications and thus the underlying scientifi c issues that sit at the intersections among biomedical science, patient care, public health, and information technology. It is no longer necessary to argue that it has become impossible to practice modern medicine, or to conduct modern biological research, without information technologies. Since the initiation of the human genome project two decades ago, life scientists have been generating data at a rate that defi es traditional methods for information management and data analysis. Health professionals also are constantly reminded that a large percentage of their activities relates to information management—for example, obtaining and recording information about patients, consulting colleagues, reading and assessing the scientifi c literature, planning diagnostic procedures, devising strategies for patient care, interpreting results of laboratory and radiologic studies, or conducting case-based and population-based research. It is complexity and uncertainty, plus society’s overriding concern for patient well-being, and the resulting need for optimal decision making, that set medicine and health apart from many other information- intensive fi elds. Our desire to provide the best possible health and health care for our society gives a special signifi cance to the effective organization and management of the huge bodies of data with which health professionals and biomedical researchers must deal. It also suggests the need for specialized approaches and for skilled scientists who are knowledgeable about human biology, clinical care, information technologies, and the scientifi c issues that drive the effective use of such technologies in the biomedical context.
Computer Applications in Health Care and Biomedicine
Keywords: Biomedical research